Islamic Counseling Using Wudhu Therapy To Reduce Sleep Disorders Of Junior High School Students - Syahminan, Ahmad; Mahfuzh, Taufik Warman; Mz, Ihsan (Syams, 2022)
The purpose of this research was to know the effect of Wudhu theraphy on sleep disorders of the students of Islam Nurul Ihsan Junior High School Palangka Raya. The decrease in students